2019
DOI: 10.1186/s13048-019-0483-7
|View full text |Cite
|
Sign up to set email alerts
|

Low dose human chorionic gonadotropin administration at the time of gonadotropin releasing-hormone agonist trigger versus 35 h later in women at high risk of developing ovarian hyperstimulation syndrome – a prospective randomized double-blind clinical trial

Abstract: BackgroundOvarian hyperstimulation syndrome remains a serious complication during in vitro fertilization cycles if high dose human chorionic gonadotropin (hCG) is used to trigger ovulation in high responder patients. Though much of this risk is mitigated with trigger using gonadotropin releasing-hormone (GnRH) agonist alone, it may result in lower birth rates. GnRH-agonist trigger and adjuvant low dose hCG has been proposed to improve birth rates, but timing of this hCG support to corpus luteum function has ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…In addition, it is important to note that both study groups exceeded expectations for both CPR and LBR compared with our center’s overall success rate in women <35 years old undergoing fresh autologous ET. This finding correlates with multiple research studies that showed that dual trigger improves IVF outcomes ( 38 , 39 , 40 , 41 , 42 , 43 ). Included in these studies was a double-blind, randomized, controlled trial that showed that the use of dual trigger had a significantly higher number of M2 oocytes retrieved, CPR, and LBR compared with those of hCG only trigger ( 40 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, it is important to note that both study groups exceeded expectations for both CPR and LBR compared with our center’s overall success rate in women <35 years old undergoing fresh autologous ET. This finding correlates with multiple research studies that showed that dual trigger improves IVF outcomes ( 38 , 39 , 40 , 41 , 42 , 43 ). Included in these studies was a double-blind, randomized, controlled trial that showed that the use of dual trigger had a significantly higher number of M2 oocytes retrieved, CPR, and LBR compared with those of hCG only trigger ( 40 ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is important to note that both study groups exceeded expectations for both CPR and LBR compared with our center's overall success rate in women <35 years old undergoing fresh autologous ET. This finding correlates with multiple research studies that showed that dual trigger improves IVF outcomes (38)(39)(40)(41)(42)(43). Included in these studies was TABLE 2 Clinical characteristics of cycles that did and did not achieve a live birth.…”
Section: Discussionsupporting
confidence: 73%
“…25,26 In the modern patient-tailored IVF treatment, the selection of the ovulation trigger strategy remains relevant, because no ovulation trigger agent can be generally recommended for the universal use. 27,28 Furthermore, according to the European Society of Human Reproduction and Embryology guideline: ovarian stimulation for IVF/ICSI recommended future research focus on GnRHa trigger with adjusted luteal support compared to full dose hCG trigger with freeze-all in observed high responder. 29 The aim of this prospective observational study was to evaluate levels of angiogenic cytokines either as a low-dose bolus or dual trigger in high-risk patients after GnRHa agonist triggering and hCG co-administration versus the standard hCG trigger.…”
mentioning
confidence: 99%
“…A new single-center prospective study demonstrates no significant differences in pregnancy rates between the two protocols comparing 1,000 vs 1,500 IU of hCG, with no statistically significant higher incidence of OHSS in the group of hCG ap-plied on OPU day compared to the group of Dual trigger. This demonstrates that either protocol may be a reliable option for patients at risk of OHSS who desire a fresh transfer (23).…”
Section: Discussionmentioning
confidence: 87%